Cactus gekweekt door Van Zutphen in 1936. Fonds ten behoeve van tandheelkundige hulp aan Zonnestraal-patiënten - Buys, A.,
Cactus gekweekt door Van Zutphen in 1936. Fonds ten behoeve van tandheelkundige hulp aan Zonnestraal-patiënten.